Recent Advances on High-Order Dipolar Annulations of Donor–Acceptor Cyclopropanes/Cyclobutanes - Yang, Liangliang; Wang, Haiyang; Lang, Ming; Peng, Shiyong (Synthesis, 2023)
This short review summarizes the recent impressive developments on the high-order dipolar annulations (HODAs) of donor–acceptor cyclopropanes (DACs) and donor–acceptor cyclobutanes (DABs) to afford medium-sized (hetero)cycles.1 Introduction2 (3+m) (m > 3) Annulations of Donor–Acceptor Cyclopropanes2.1 (3+4) Annulations2.2 (3+5) Annulations3 (4+m) (m > 2) Annulations of Donor–Acceptor Cyclobutanes4 Conclusion
Keywords: high-order dipolar annulation; donor–acceptor; cyclopropanes; cyclobutanes; cyclization